Towards an Embodied Signature of Improvisation Skills - Coste, Alexandre; Bardy, Benoît G.; Marin, Ludovic (Frontiers in Psychology, 2019)
Improvisation is not limited to performing arts but is extended to everyday life situations such as conversations or decision-making. Due to their ubiquitous nature, improvisation skills have received increasing attention from psychologist researchers over the last decade. A core challenge is to grasp the complex creative process involved in improvisation performance. To date, most studies have attempted to provide insight on brain activity and perceptual experiences when perceiving a performance, especially in musical or artistic form. However, these experiences are quite different from the full performance as performers and are far from daily life situations. In this Perspective, we show how researchers have often missed key points concerning the study of improvisation skills, especially by ignoring the central role of bodily experiences in their formation. Furthermore, we consider how the study of (neglected) motor component of improvisation performance can provide valuable insights into the underlying nature of creative process involved in improvisation skills and their acquisition. Finally, we propose a roadmap for studying improvisation from the acquisition of kinematic data in an ecological context to analysis, including the consideration of the coalition of (individual, environmental and task) constraints in the emergence of improvised behaviours.